2013
DOI: 10.1016/j.drugalcdep.2013.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns of first injection across key periods of the French Harm Reduction Policy: PrimInject, a cross sectional analysis

Abstract: Conclusion:The PrimInject study showed that there is a group of injection drug users that is larger than the group of injection drug users observed in previous studies; therefore, it is necessary to diversify programs to reach the entire spectrum of high-risk users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…Similarly to previous studies (Guichard et al, 2013;Roy et al, 2002;Vlahov et al, 1991), we found that the drug market period in which injecting initiation took place was associated with the type of drug used at injecting initiation. This finding is reasonably unsurprising.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similarly to previous studies (Guichard et al, 2013;Roy et al, 2002;Vlahov et al, 1991), we found that the drug market period in which injecting initiation took place was associated with the type of drug used at injecting initiation. This finding is reasonably unsurprising.…”
Section: Discussionsupporting
confidence: 73%
“…Studies conducted in North America have demonstrated a close association between fluctuations in cocaine markets and the likelihood that IDU initiation involved cocaine injection (Roy et al, 2002;Vlahov, Anthony, Celentano, Solomon, & Chowdhury, 1991). More recently, Guichard et al (2013) examined characteristics of injecting initiation among French drug users who initiated injecting across four time periods defined by changes in drug policy. Their findings indicated changing patterns of initiation: although heroin was the most commonly used drug at initiation across all periods, the proportion of participants who reported initiating injecting with other drugs increased over time.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, the association between patient age at first drug use and longer intended treatment duration is unlikely to be an extension of the association between patient age and better treatment outcomes with BMT (Dreifuss et al, 2013). The average age of first opioid use has been increasing over time (Cicero, Ellis, Surratt, & Kurtz, 2014; Guichard et al, 2013), and this trend could indicate that increases in retention in OMT may also be observed.…”
Section: Discussionmentioning
confidence: 99%
“…To document the profile of new initiates, the PrimInject study was carried out using the Internet to reach current or former injectors and obtain descriptions of circumstances, behaviours, and potential exposure to blood-borne infections at the time of injection initiation. Launched within the context of changing trends in substance use, drug policy, and drug supply, PrimInject was the first study to describe new injectors and the circumstances surrounding their first injections over time [ 40 ]. The aim of this exploratory analysis is to examine injection risk behaviours and correlates at the time of initiation into injection drug use among individuals who began injection in the post-2000 era in France.…”
Section: Introductionmentioning
confidence: 99%